2022
DOI: 10.1038/s41528-022-00135-1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical graphene on flexible substrate, overcoming limits of crack-based resistive strain sensors

Abstract: Resistive strain sensors (RSS) with ultrasensitivity have attracted much attention as multifunctional sensors. However, since most ultrasensitive RSS are designed by cracked conductive metals, the sensing performance is severely degraded due to accumulated structural deformation with consecutive cycles. To overcome such limitation, newly designed structures have been suggested, but the development of mechanosensors exhibiting superior stability and ultrasensitivity still remains a challenge. Here, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Physical sensing is another area where 2D material-based sensors declared their superiority. The mechanical and electrical robustness of 2D materials allows them to be highly responsive to various physical stimuli. , Integrated with system-level readout, processing, and transmission capabilities, these devices show great potential for various applications, including motion sensors, e-skins, etc. , Sun et al demonstrated a graphene-based dual-function acoustic transducer with machine learning-assisted human–robot interface (Figure c) . The graphene-based device was able to perform as both a self-powered microphone and speaker via the triboelectric and thermoacoustic effects.…”
Section: Applications For Flexible Electronicsmentioning
confidence: 99%
“…Physical sensing is another area where 2D material-based sensors declared their superiority. The mechanical and electrical robustness of 2D materials allows them to be highly responsive to various physical stimuli. , Integrated with system-level readout, processing, and transmission capabilities, these devices show great potential for various applications, including motion sensors, e-skins, etc. , Sun et al demonstrated a graphene-based dual-function acoustic transducer with machine learning-assisted human–robot interface (Figure c) . The graphene-based device was able to perform as both a self-powered microphone and speaker via the triboelectric and thermoacoustic effects.…”
Section: Applications For Flexible Electronicsmentioning
confidence: 99%
“…Piezoresistive strain sensors have been highlighted as successful candidates owing to their straightforward structure, which converts physical signals into digital data without additional circuits or attachments. In particular, crack-based sensors using various materials, such as metal, 16−18 graphene, 19 and carbon nanotube, 20,21 have shown excellent capabilities in detecting subtle vibrations. Recently, nanoparticles (NPs) have been considered promising building blocks for realizing highly sensitive strain sensors owing to their solution processability and interparticle distance-dependent transport, enabling lowcost and high-sensitivity sensor fabrication.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Piezoresistive strain sensors have been highlighted as successful candidates owing to their straightforward structure, which converts physical signals into digital data without additional circuits or attachments. In particular, crack-based sensors using various materials, such as metal, graphene, and carbon nanotube, , have shown excellent capabilities in detecting subtle vibrations. Recently, nanoparticles (NPs) have been considered promising building blocks for realizing highly sensitive strain sensors owing to their solution processability and interparticle distance-dependent transport, enabling low-cost and high-sensitivity sensor fabrication. The advancement of crack-based sensors has significantly enhanced our understanding of human voice by enabling detailed linguistic analysis through direct detection of vocal cord vibrations to the state of utilizing spectrogram. , However, the nonzero interparticle distances induce high electrical resistances, leading to large power consumption, poor readability, and low signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It refer to the integration of different material systems and different functional units on flexible substrates to form flexible information devices and electronic systems which can be stretched, bent and twisted [1]. Flexible electronic devices not only have stable functionality with traditional electronic devices, but also have the characteristics of light weight, softness, and perfect fit with the surface of the human body [2][3], which greatly promotes the ternary integration of human-machine-material. It will have a huge impact in many fields such as intelligent technology, health care, and brain-computer fusion.…”
Section: Introductionmentioning
confidence: 99%